Relevansi Pemikiran Ekonomi Al-Ghazal terhadap Etika Bisnis di Era Modern - Salwa Latifa Zahra; Lina Marlina Susana (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2026)
This study examines the relevance of al-Ghazali's economic thought to business ethics in the modern era using qualitative methods based on a literature review. Al-Ghazali, one of the most influential scholars in the Islamic intellectual tradition, is known not only for his Sufism and philosophy but also for his significant contributions to economic thought and social ethics. This study aims to explore al-Ghazali's Islamic economic principles—particularly the values ​​of justice, honesty, trustworthiness, social responsibility, and equitable distribution of wealth—and analyze how these principles can be applied in contemporary business practices. The study begins with a brief biography of al-Ghazali, his intellectual journey, and his contributions through monumental works such as Ihya' 'Ulum al-Din and al-Mustasfa. The analysis shows that al-Ghazali emphasized the importance of balancing spiritual and material needs in economic activities. He emphasized the prohibition of harmful practices, such as fraud, usury, market manipulation, and exploitation, and encouraged fairness in all economic transactions. Ethical values ​​such as integrity, trustworthiness, and concern for the welfare of society are important foundations in his economic thought framework. These principles have proven relevant to addressing the increasingly complex challenges of modern business practices, particularly in the context of moral crises, unequal distribution of wealth, and unsustainable business practices. Applying al-Ghazali's thinking can help build a business system that is ethical, just, sustainable, and oriented toward the common good. Thus, al-Ghazali's economic thought remains relevant and serves as an important reference in shaping civilized business ethics in the contemporary era. Abstrak Penelitian ini mengkaji relevansi pemikiran ekonomi al-Ghazali terhadap etika bisnis di era modern dengan menggunakan metode kualitatif berbasis kajian pustaka. Al-Ghazali, salah satu ulama paling berpengaruh dalam tradisi intelektual Islam, tidak hanya dikenal dalam bidang tasawuf dan filsafat, tetapi juga memberikan kontribusi penting dalam pemikiran ekonomi dan etika sosial. Kajian ini bertujuan menggali prinsip-prinsip ekonomi Islam menurut al-Ghazali—terutama nilai keadilan, kejujuran, amanah, tanggung jawab sosial, serta distribusi kekayaan yang adil—dan menganalisis bagaimana prinsip tersebut dapat diterapkan dalam praktik bisnis kontemporer. Penelitian diawali dengan penelusuran biografi singkat al-Ghazali, perjalanan intelektualnya, serta kontribusinya melalui karya monumental seperti Ihya’ ‘Ulum al-Din dan al-Mustasfa. Hasil analisis menunjukkan bahwa al-Ghazali menekankan pentingnya keseimbangan antara kebutuhan spiritual dan material dalam aktivitas ekonomi. Ia menegaskan larangan terhadap praktik yang merugikan, seperti penipuan, riba, manipulasi pasar, dan eksploitasi, serta mendorong keadilan dalam setiap transaksi ekonomi. Nilai-nilai etika seperti integritas, amanah, dan kepedulian terhadap kesejahteraan masyarakat menjadi landasan penting dalam kerangka pemikiran ekonominya. Prinsip-prinsip tersebut terbukti relevan untuk menghadapi tantangan praktik bisnis modern yang semakin kompleks, terutama dalam konteks krisis moral, ketimpangan distribusi kekayaan, dan praktik bisnis yang tidak berkelanjutan. Penerapan pemikiran al-Ghazali dapat membantu membangun sistem bisnis yang etis, adil, berkelanjutan, dan berorientasi pada kemaslahatan bersama. Dengan demikian, pemikiran ekonomi al-Ghazali tetap aktual dan menjadi rujukan penting dalam membentuk etika bisnis yang berkeadaban di era kontemporer.